CREATINE USE IN SPORTS: SAFETY AND MECHANISMS OF ACTION - Paweł Radkowski; Adam Rafałowicz; Urszula Justyna Wojciechowska; Magdalena Rafałowicz; Łukasz Grabarczyk (International Journal of Innovative Technologies in Social Science, 2025)
Background: Creatine was first isolated from muscle in 1832 and now is a globally popular ergogenic supplement, valued at USD 1.11 billion in 2024 and projected to reach USD 4.21 billion by 2030. It functions as a rapidly mobilizable energy reserve via the phosphocreatine system and modulates Ca²⁺ handling in muscle cells. Aim: This study present the current knowledge on creatine supplementation, its prevalence, mechanisms of action, effects on performance and muscle growth and safety profile. Material and methods: A literature review of studies published in the PubMed and Google Scholar databases was conducted, analysing clinical trials, meta-analyses, and systematic reviews concerning creatine metabolism, dosing strategies, performance outcomes (anaerobic, strength, aerobic), hypertrophy and adverse effects. Results: Creatine supplementation improves short-burst efforts and strength, however moderately enhances and even can decrease endurance. Creatine also has anabolic properties and can improve gains in muscle mass. Dosing regimens reliably elevate intramuscular stores within days (loading) or weeks (daily use). Side effects are generally conducted to transient water retention and gastrointestinal symptoms, with no evidence of renal or hepatic harm. Conclusions: Creatine is a safe, well-researched supplement that can enhance anaerobic capacity, muscular strength, and hypertrophy when used in appropriate dosing protocols. Its benefits for prolonged aerobic exercise are modest, but users should expect temporary weight gain, that can decrease endurance.